Penerapan Teknik Modeling Simbolis Dalam Pengembangan Perencanaan Karier Siswa SMPN 6 Palangka Raya - Yulia Yulia; Helmuth Y Bunu; Mimi Suriatie; Makda del Lena; Rahmaniah Samuda (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
Career planning is something that concerns the future in the long term. It must be planned in advance; to plan where someone wants to go and what he wants to achieve.The purpose of this study was to determine the effectiveness of symbolic modeling techniques in the development of student career planning; to choose further studies that suit their interests and talents. The type of the research is qualitative research with observation, interview, and documentation methods. The research subjects were 5 students. This research was carried out based on the phenomenon at SMP Negeri 6 Palangka Raya, where there were students who were still confused about choosing further studies according to their interests and talents. The results showed that after being given symbolic modeling with videos, students experienced changes such as: (1) Students were able to understand their strengths and weaknesses in certain fields; (2) Students begin to be able to plan careers after graduating from school; (3) Students were able to prepare options for the next level of study. From these data the researchers concluded that symbolic modeling was effective in helping students at SMP Negeri 6 Palangka Raya in planning their careers.